2019
DOI: 10.1002/dc.24334
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine carcinoma diagnosis from bile duct cytological specimens: A retrospective single‐center study

Abstract: Neuroendocrine carcinoma (NEC) in the extrahepatic bile duct is extremely rare and clinically aggressive. Cytological examination of bile and/or bile duct brushing specimens plays an important role in the diagnosis of carcinoma of the extrahepatic bile duct, but only a few articles have described the cytological features of NEC in this area. Thus, we retrospectively analyzed the cytological features of NEC in bile and/or bile duct brushing specimens. Patients with a histopathological diagnosis of NEC who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Sano et al [ 15 ] reported a case of well-differentiated EBNET diagnosed successfully by EUS-guided fine-needle aspiration biopsy. Besides, biliary brush cytology has been widely used in the preoperative diagnosis of biliary diseases, and the cytology of bile and bile duct brush specimens were also helpful for preoperative diagnosis of biliary NET [ 10 , 16 ]. We regretted that the patient did not have bile juice cytology and step biopsy before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Sano et al [ 15 ] reported a case of well-differentiated EBNET diagnosed successfully by EUS-guided fine-needle aspiration biopsy. Besides, biliary brush cytology has been widely used in the preoperative diagnosis of biliary diseases, and the cytology of bile and bile duct brush specimens were also helpful for preoperative diagnosis of biliary NET [ 10 , 16 ]. We regretted that the patient did not have bile juice cytology and step biopsy before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most reported cases were resected with a diagnosis of cholangiocarcinoma and diagnosed with NEC after surgery. [1][2][3][4][5] This paper reports the case of an 84-year-old female with small-cell NEC of the extrahepatic bile duct, confirmed by a biopsy from an ERCP, with a review of the relevant literature on this condition.…”
Section: Introductionmentioning
confidence: 99%